Differential transcription profiles in Aedes aegypti detoxification genes after temephos selection. Issue 2 (3rd December 2013) - Saavedra‐Rodriguez, K.; Strode, C.; Flores, A. E.; Garcia‐Luna, S.; Reyes‐Solis, G.; Ranson, H.; Hemingway, J.; Black, W. C.
Abstract The mosquito Aedes aegypti is the main vector of Dengue and Yellow Fever flaviviruses. The organophosphate insecticide temephos is a larvicide that is used globally to control Ae. aegypti populations; many of which have in turn evolved resistance. Target site alteration in the acetylcholine esterase of this species has not being identified. Instead, we tracked changes in transcription of metabolic detoxification genes using the Ae. aegypti 'Detox Chip' microarray during five generations of temephos selection. We selected for temephos resistance in three replicates in each of six collections, five from Mexico, and one from Peru. The response to selection was tracked in terms of lethal concentrations. Uniform upregulation was seen in the epsilon class glutathione‐S‐transferase (eGST) genes in strains from Mexico prior to laboratory selection, while eGSTs in the Iquitos Peru strain became upregulated after five generations of temephos selection. While expression of many carboxyl/cholinesterase esterase (CCE) genes increased with selection, no single esterase was consistently upregulated and this same pattern was noted in the cytochrome P450 monooxygenase (CYP) genes and in other genes involved in reduction or oxidation of xenobiotics. Bioassays using glutathione‐S‐transferase (GST), CCE and CYP inhibitors suggest that various CCEs instead of GSTs are the main metabolic mechanism conferring resistance to temephos. We show that temephos‐selected strains show no cross resistance to permethrin and that genes associated with temephos selection are largely independent of those selected with permethrin in a previous study.